Functional Evaluation and Genetic Evolution of Human T-Cell Responses After Vaccination With a Conditionally Replication-Defective Cytomegalovirus Vaccine. (8th October 2020) - Cox, Kara S; Zhang, Lu; Freed, Daniel C; Tang, Aimin; Zhang, Shifang; Zhou, Yu; Wang, I-Ming; Rupp, Richard E; Adler, Stuart P; Musey, Luwy K; Wang, Dai; Vora, Kalpit A; et al.
Abstract: Background: Cytomegalovirus (CMV) can cause congenital infection and is the leading cause of nongenetic newborn disabilities. V160, a conditionally replication-defective virus, is an investigational vaccine under evaluation for prevention of congenital CMV. The vaccine was well tolerated and induced both humoral and cellular immunity in CMV-seronegative trial participants. T-cell–mediated immunity is important for immune control of CMV. Here we describe efforts to understand the quality attributes of the T-cell responses induced by vaccination. Methods: Using multicolor flow cytometry, we analyzed vaccine-induced T cells for memory phenotype, antigen specificity, cytokine profiles, and cytolytic potential. Moreover, antigen-specific T cells were sorted from 4 participants, and next-generation sequencing was used to trace clonal lineage development during the course of vaccination using T-cell receptor β-chain sequences as identifiers. Results: The results demonstrated that vaccination elicited polyfunctional CD4 and CD8 T cells to 2 dominant antigens, pp65 and IE1, with a predominantly effector phenotype. Analysis of T-cell receptor repertoires showed polyclonal expansion of pp65- and IE1-specific T cells after vaccination. Conclusion: V160 induced a genetically diverse and polyfunctional T-cell response and the data support further clinical development of V160 for prevention of CMV infection and congenital transmission. Clinical Trials Registration: NCT01986010. Abstract : T-cell responses to a cytomegalovirus (CMV) vaccine, V160, were evaluated in baseline CMV-seronegative participants. Polyfunctional CD4 and CD8 T cells with a predominantly effector phenotype were demonstrated. Analysis of T-cell receptor repertoires showed postvaccination polyclonal expansion of CMV-specific T cells.